Seven Cases of Living Parental Small Bowel Transplantation Donors: Perioperative Care in 3D Laparoscopic Live Donor Ileal Resection - Dongling Shao, BSN; Qunmin Wang, MSN; Shuting Sun, MSN; Chaoxu Liu, PhD; Ge Sun, PhD (Transplantation Direct)
Background. Although small bowel transplantation is generally a highly effective treatment for patients with irreversible intestinal failure, and it is the only viable recourse for the restoration of intestinal function, the quantity of individuals awaiting a transplant surpasses that of accessible donors. With the advent of living donor small bowel transplantation, the small bowel transplant donor pool has been expanded to include parental donors. However, its global implementation is constrained by concerns regarding remaining donor safety and long-term prognoses. To help the donor recover better in the future, we have used 3-dimensional (3D) laparoscopic live donor ileal resection. Methods. This study reviews 7 cases at our hospital involving living parental donors for small bowel transplantation. Each donor, being a close relative of the recipient, voluntarily provided a portion of their intestine. We used 3D laparoscopic ileal resection under general anesthesia to enable minimally invasive procedures, reduce surgical trauma, and expedite recovery. Comprehensive preoperative evaluations included psychological counseling to ensure informed consent, whereas postoperative care focused on tailored rehabilitation, nutritional support, bowel function monitoring, and psychological health. Results. All donors recovered successfully without severe perioperative complications. At 6 mo postsurgery, all donors had normal bowel function and reported no issues with malabsorption or gastrointestinal health. Psychological assessments indicated good mental health and high satisfaction with their decision to donate. Conclusions. Three-dimensional laparoscopic ileal resection for living parental donors is both feasible and safe, offering a minimally invasive approach with favorable donor outcomes. One-year follow-ups confirm that this technique provides high-quality grafts for recipients while preserving donor health and well-being. These findings support the potential for broader adoption of 3D laparoscopic ileal resection in living donor small bowel transplantation, with larger cohort studies recommended to validate these outcomes and refine donor care practices.